P191 Paget trial: topical 5% imiquimod for vulvar paget disease, first results of clinical efficacy. (1st November 2019) - van der Linden, M; Meeuwis, K; van Hees, C; van Dorst, E; Bulten, J; Bosse, T; IntHout, J; Boll, D; van Beurden, M; Oonk, M; van Poelgeest, M; de Hullu, J
Abstract : Introduction/Background: Vulvar Paget disease (VPD) is a rare skin disorder, which is most common in postmenopausal Caucasian women. They usually present with an erythematous plaque that may show typical 'cake icing' scaling and may cause itching, or a burning sensation. Although most cases are noninvasive, VPD may be invasive or associated with an underlying vulvar or distant adenocarcinoma. Treatment of choice is wide local excision with negative margins. Obtaining clear surgical margins is challenging and may lead to extensive and mutilating surgery. Recurrence rates are high, about 35%, which emphasizes the need for new treatment options. A number of reports, have shown promising results using the topical immune response modifier imiquimod. This study aimed to investigate the efficacy, safety, and immunological response in patients with noninvasive VPD using a standardized treatment schedule with 5% imiquimod cream. Methodology: The Paget Trial (NCT02385188 ) is a multicenter observational cohort study including seven tertiary referral hospitals in the Netherlands. Twenty-four patients with noninvasive VPD were treated with topical 5% imiquimod cream three times a week for 16 weeks. The primary efficacy outcome was the reduction in lesion size at 12 weeks after end of treatment. Results: The median age at time of enrollement was 67 (42–84). After treatment with topical 5% imiquimod cream 12 patients (52, 2%) had a complete response and 7 patients (30, 4%) a partial response. Patients experienced side effects like fatigue, headaches, and almost 80% needed painkillers during treatment. Eight patients adjusted the treatment protocol to two applications a week, and three patients stopped treatment because of the side effects. We found no clear difference in the effect of treatment between patients who used topical 5% imiquimod cream two or three times a week, see table 1. Conclusion: Topical 5% imiquimod cream seems to be an effective treatment for VPD with a response rate of 82, 6%. Disclosure: MvdL nothing to declare. KM Consultant and received honoraria from Lilly and Eucerin and advisor for Eucerin, Netherlands. CvH nothing to declare. EvD nothing to declare. JB nothing to declare. TB nothing to declare. JitH nothing to declare. DB nothing to declare. MvB nothing to declare. MvP nothing to declare. JdH nothing to declare.